The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1109/access.2021.3052478
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Methodologies in Agriculture for Soil Moisture and Nutrient Monitoring

Abstract: Development and deployment of sensing technologies is one of the main steps in achieving sustainability in crop production through precision agriculture. Key sensing methodologies developed for monitoring soil moisture and nutrients with recent advances in the sensing devices reported in literature using those techniques are overviewed in this article. The soil moisture determination has been divided into four main sections describing soil moisture measurement metrics and laboratory-based testing, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 127 publications
0
38
0
Order By: Relevance
“…Soil characteristics are of a great importance in many applied fields, such as agriculture [1], construction [2], and earthing installation [3]. One of the important physical properties of soil is the electrical resistivity (ρ), which can be defined as the resistance in ohms between the opposite faces of a unit cube of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Soil characteristics are of a great importance in many applied fields, such as agriculture [1], construction [2], and earthing installation [3]. One of the important physical properties of soil is the electrical resistivity (ρ), which can be defined as the resistance in ohms between the opposite faces of a unit cube of the material.…”
Section: Introductionmentioning
confidence: 99%
“…This article focuses primarily on the sensing methodologies developed in agriculture for monitoring diseases and stress caused due to biotic aggressors-pathogens and pests. A recent article by our group provided a comprehensive survey of soil moisture and nutrient sensing that cover the key abiotic sources of stress [19]. This section presents an overview of the responses of biotic stresses in plants that enables the development of technologies to detect them.…”
Section: How Do Plants Respond To Stress?mentioning
confidence: 99%
“…Methodologies enabling early and accurate detection of plant stress due to pathogens and pests provide a way for optimal deployment of countermeasures for reducing of losses in yield. Our group has been pursuing agriculture sensor design for soil [5][6][7][8][9][10][11][12][13][14][15][16][17] and plant health [18][19][20][21][22][23][24][25][26], modeling for soil moisture/nutrients and plant growth dynamics [27,28], and decision-making for irrigation and fertilization for over a decade [27,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, certain traits can be understood with the help of three phenomena: reflectance, absorption, and emittance, that occur naturally in all plants [ 6 ]. The current record on the advancements in agriculture instrumentation shows that all these phenomena can be captured with the help of imaging sensors [ 7 ]. It has been found that the best way to quantify water stress in plants is by measuring the reemittance of light from the plant surface.…”
Section: Introductionmentioning
confidence: 99%